Impact of Simulated Gastrointestinal Conditions on Antiglycoxidant and α-Glucosidase Inhibition Capacities of Cyanidin-3-O-Glucoside - Didier Fraisse (MDPI AG, 2021)
Cyanidin-3-O-glucoside (C3G) is a widespread anthocyanin derivative, which has been reported in vitro to exert potent antioxidant, antiglycation and α-glucosidase inhibition effects. Nevertheless, the physiological relevance of such properties remains uncertain considering its significant instability in gastrointestinal conditions. A simulated digestion procedure was thus instigated to assess the influence of gastric and intestinal media on its chemical integrity and biological activities. HPLC analyses of digested C3G samples confirmed the striking impact of intestinal conditions, as attested by a decomposition ratio of 70%. In contrast, with recovery rates of around 90%, antiglycation, as well as DPPH and ABTS scavenging assays, uniformly revealed a noteworthy persistence of its antiglycoxidant capacities. Remarkably, a prominent increase of its α-glucosidase inhibition activity was even observed after the intestinal phase, suggesting that classical in vitro evaluations might underestimate C3G antidiabetic potential. Consequently, the present data provide novel and specific insights on C3G’s digestive fate, suggesting that the gastrointestinal tract does not profoundly affect its positive action on oxidative and carbonyl stresses. More specifically, it also tends to support its regulating effects on postprandial hyperglycemia and its potential usefulness for diabetes management.